2012
DOI: 10.1111/j.1440-1681.2011.05632.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal syndrome: Pathophysiology, preclinical models, management and potential role of uraemic toxins

Abstract: Cardiorenal syndrome (CRS) describes the primary dysfunction in either the kidney or heart that initiates the combined impairment of both organs. The heart and kidney exert reciprocal control of the respective function to maintain constant blood volume and organ perfusion under continuously changing conditions. The pathophysiology of CRS is not fully understood, but appears to be caused by a complex combination of haemodynamic, neurohormonal, immunological and biochemical feedback pathways. Of these pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 133 publications
(286 reference statements)
0
16
0
Order By: Relevance
“…Previous studies that evaluated consequences of combined renal and myocardial damage were mainly focused on cardiac function parameters and on the infarct size. While the majority of studies demonstrated that after myocardial infarction the renal damage is exacerbated and in animals with renal injury the infarct size is greater, others either failed to demonstrate worsening of myocardial infarction after renal damage in 5/6 NX rats, or found that infarct size in 5/6 NX rats was the same as in sham‐operated rats, and cardioprotective effects of ischemic preconditioning were maintained . The latter reports contradicted the common opinion that heart and kidney diseases reciprocally deteriorate their respective outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that evaluated consequences of combined renal and myocardial damage were mainly focused on cardiac function parameters and on the infarct size. While the majority of studies demonstrated that after myocardial infarction the renal damage is exacerbated and in animals with renal injury the infarct size is greater, others either failed to demonstrate worsening of myocardial infarction after renal damage in 5/6 NX rats, or found that infarct size in 5/6 NX rats was the same as in sham‐operated rats, and cardioprotective effects of ischemic preconditioning were maintained . The latter reports contradicted the common opinion that heart and kidney diseases reciprocally deteriorate their respective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure (CHF) and chronic kidney disease (CKD) present serious medical problems to millions of patients worldwide, with an incidence increasing over time; the patients with CHF and CKD combined are known to exhibit extremely poor survival prognosis, worse than that of most patients with diagnosed cancers . Previous studies have clearly demonstrated that progression of CHF as well as of CKD is accelerated by hypertension and inappropriately increased activity of the renin‐angiotensin system (RAS), therefore RAS blocking agents are currently applied as a golden standard therapy of CHF and CKD . However, the effectiveness of renoprotective action of RAS inhibition is limited, especially in the advanced phase of CKD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further uremic toxins that could contribute to anemia in chronic kidney disease is indoxyl sulfate [39,40], which is at least partially effective by suppression of erythropoietin production [41]. Further effects of indoxyl sulfate include downregulation of Klotho [42], induction of oxidative stress [42,43], up-regulation of NFκB [42], aortic calcification and aortic wall thickening [42], interference with wound repair [44], triggering of cell senescence [42], stimulation of cardiac and renal fibrosis [42,45] and acceleration of renal disease progression [42]. Indoxyl sulfate is generated by colonic microbes [46] and accumulates in blood, if renal excretion is impaired [42].…”
Section: Introductionmentioning
confidence: 99%
“…9 Deregulation of haemodynamic, neurohormonal, immunological and biochemical feedback pathways has been suggested to be among the factors contributing to the pathogenesis of cardiorenal syndrome (CRS), which is characterized by initial dysfunction in either the kidney or heart that initiates progressive impairment of both organs. Liu et al 10 describe a novel aspect of the role of uraemic toxins that accumulate in CRS with indoxyl sulphate being found to have direct adverse effects on cardiac cells. These studies may suggest a new window of opportunity in the early diagnosis of CRS for the assessment of biomarkers for cardiac and renal injury.…”
mentioning
confidence: 99%